Variations in maternal care alter corticosterone and 17beta-estradiol levels, estrous cycle and folliculogenesis and stimulate the expression of estrogen receptors alpha and beta in the ovaries of UCh rats - Amorim, Joao P. A.; Chuffa, Luiz G. A.; Teixeira, Giovana R. [UNESP]; Mendes, Leonardo O.; Fioruci, Beatriz A.; Martins, Otavio A. [UNESP]; Mello Júnior, Wílson de [UNESP]; Anselmo-Franci, Janete A.; Pinheiro, Patricia F. F. [UNESP]; Martinez, Marcelo; Martinez, Francisco E. [UNESP] (Biomed Central Ltd., 2011)
Background: Variations in maternal care are associated with neonatal stress, hormonal disturbances and reproductive injuries during adulthood. However, the effects of these variations on sex hormones and steroid receptors during ovary development remain undetermined. This study aimed to investigate whether variations in maternal care are able to influence the hormonal profile, follicular dynamics and expression of AR, ER-alpha and ER-beta in the ovaries of UCh rat offspring.Methods: Twenty-four adult UCh rats, aged 120 days, were randomly divided into two groups (UChA and UChB) and mated. Maternal care was assessed from birth (day 0) to the 10th postnatal day (PND). In adulthood, twenty adult female rats (UChA and UChB offspring; n = 10/group), aged 120 days, were euthanized by decapitation during the morning estrus.Results: UChA females (providing high maternal care) more frequently displayed the behaviors of carrying pups, as well as licking/grooming and arched back nursing cares. Also, mothers providing high care had elevated corticosterone levels. Additionally, offspring receiving low maternal care showed the highest estrous cycle duration, increased corticosterone and 17beta-estradiol levels, overexpression of receptors ER-alpha and ER-beta, increased numbers of primordial, antral and mature follicles and accentuated granulosa cell proliferation.Conclusions: Our study suggests that low maternal care alters corticosterone and 17beta-estradiol levels, disrupting the estrous cycle and folliculogenesis and differentially regulating the expression of ER-alpha and ERbeta in the ovaries of adult rats.
Keywords: maternal care; sex steroid receptors; corticosterone; E2; ovary